PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Verawaty Verawaty; Ade Kemala Jaya; Tita Mendala (Akuisisi: Jurnal Akuntansi, 2015)
The research is aimed to analyze the influences of financial performance to the company stocks return. The sample is mining companies listed in the Indonesia Stock Exchange in 2013. The study concluded that at the significant level (α) of 5%, there are no significant influences between DER (Debt to Equity Ratio), REO (Return on Equity), EPS (Earning Per Share), PER (Price Earning Ratio) and NPM (Net Profit Margin) to the stocks return. The results are related to the decrease of mining commodities in international market since 2012, the government’s plans to implement a rule banning the export of low-calorie coal, the drastic decline of exchange rate of rupiah against US dollar, the trade deficit in 2013 and world market conditions which make Indonesian exports declined.  Keywords: DER (Debt to Equity Ratio), REO (Return On Equity), EPS (Earning Per Share), PER (Price Earning Ratio), NPM (Net Profit Margin), Stocks Return